Challenging practices: experiences from community and individual living lab approaches. Issue 1 (1st January 2021) - Matschoss, Kaisa; Fahy, Frances; Rau, Henrike; Backhaus, Julia; Goggins, Gary; Grealis, Eoin; Heiskanen, Eva; Kajoskoski, Tuija; Laakso, Senja; Apajalahti, Eeva-Lotta; Genus, Audley; Godin, Laurence; et al.
Abstract: In this article, we examine a change initiative designed to involve households in testing ways to transform two everyday practices ‒ heating and doing laundry. The research design included an examination of the challenges of changing practices either in a setting that fosters collective engagement or with individual households. Two different types of living labs were carried out simultaneously in eight European countries in Autumn–Winter 2018. We reflect on differences in results in terms of both changes in practices and the experiences of participating households that we argue can be at least partially attributed to householders' engagement in different types of living labs. We discuss the implications of an individual-focused vs. community-oriented approach for change initiatives seeking to challenge social norms for sustainability transitions, concentrating in particular on differences in the nature of participants' engagement and their willingness and ability to challenge routine practices. This is complemented by analytical reflections on the differences in design, interaction, and performance between the two types of living labs. We show that an explicit focus on collaborative engagement in living labs can produce results that reflect shared experiences, community support, challenging established norms, and collective commitment toward change.